The Risk Factor of Malnutrition of Bajo’s Adolescents - Halifu, Ruslan; Amiruddin, Ahmad; Sudirman, Sudirman (Universitas Aisyah Pringsewu, 2022)
There are many problems in adolescence, such as malnutrition. This problem that is commonly found in tribal societies, as example is Bajo tribe societies. The family environment or parents has an important role in this problem. The objective of this study to know do there are influence behaviors of Bajo parents to fulfill the nutrition of their teenagers again malnutrition of their adolescents. Hypothesis of this study is there are influence behaviors of Bajo parents to fulfill the nutrition of their teenagers again malnutrition of their adolescents. We used the qualitative method with case study approach as the method of this study. As the results, we indicated there are influence behaviors of Bajo parents to fulfill the nutrition of their teenagers again malnutrition of their adolescents. The behaviors influenceded by various factors that are culture which risk factor again the growth and development of child, unavailability of information, income level of family that low and accessibility to go to market that difficult. These factors can be used as an approach in formulate policies or programs to resolve the nutritional adolescent problems is Bajo tribe societies. Abstrack: Ada banyak masalah yang menimpa anak usia remaja, contohnya adalah malnutrisi. Masalah ini umumnya terjadi di komunitas tribal, sebagai contohnya adalah pada komunitas Suku Bajo. Lingkungan keluarga atau orang tua memegang peranan penting terhadap masalah ini. Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh perilaku orang tua dalam memenuhi nutrisi anak remaja mereka terhadap malnutrisi anak remaja mereka. Kami menggunakan metode kualitatif dengan pendekatan studi kasus, sebagai metode penelitian ini. Sebagai hasil penelitian ini, kami menemukan bahwa ada pengaruh perilaku orang tua dalam memenuhi nutrisi anak remaja mereka terhadap malnutrisi anak remaja mereka. Perilaku orang tua tersebut dipengaruhi oleh berbagai faktor yaitu budaya yang kurang mendukung pertumbuhan dan perkembangan anak, kurangnya ketersediaan informasi, tingkat pendapatan keluarga yang rendah, dan aksesibilitas ke pusat perbelanjaan yang sulit. Berbagai faktor ini dapat digunakan untuk menyusun suatu pendekatan kebijakan atau program untuk menyelesaikan masalah nutrisi pada anak remaja pada komunitas Suku Bajo.